Micromachines for Dielectrophoresis, Volume II - Martinez-Duarte, Rodrigo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Dielectrophoresis (DEP) continues to be an effective technique for the label-free identification and manipulation of targeted particles in multiple applications. This second volume of the "Micromachines for Dielectrophoresis" series includes 13 novel contributions to the field in aspects ranging from fundamentals and theoretical modeling to applications.